Stapled Anoplin as an Antibacterial Agent - Wojciechowska, Monika; Macyszyn, Julia; Miszkiewicz, Joanna; Grzela, Renata; Trylska, Joanna (Frontiers in Microbiology, 2021)
Anoplin is a linear 10-amino acid amphipathic peptide (Gly-Leu-Leu-Lys-Arg-Ile-Lys-Thr-Leu-Leu-NH2) derived from the venom sac of the solitary wasp. It has broad antimicrobial activity, including an antibacterial one. However, the inhibition of bacterial growth requires several dozen micromolar concentrations of this peptide. Anoplin is positively charged and directly interacts with anionic biological membranes forming an α-helix that disrupts the lipid bilayer. To improve the bactericidal properties of anoplin by stabilizing its helical structure, we designed and synthesized its analogs with hydrocarbon staples. The staple was introduced at two locations resulting in different charges and amphipathicity of the analogs. Circular dichroism studies showed that all modified anoplins adopted an α-helical conformation, both in the buffer and in the presence of membrane mimics. As the helicity of the stapled anoplins increased, their stability in trypsin solution improved. Using the propidium iodide uptake assay in Escherichia coli and Staphylococcus aureus, we confirmed the bacterial membrane disruption by the stapled anoplins. Next, we tested the antimicrobial activity of peptides on a range of Gram-negative and Gram-positive bacteria. Finally, we evaluated peptide hemolytic activity on sheep erythrocytes and cytotoxicity on human embryonic kidney-293 cells. All analogs showed higher antimicrobial activity than unmodified anoplin. Depending on the position of the staple, the peptides were more effective either against Gram-negative or Gram-positive bacteria. Anoplin[5-9], with a lower positive charge and increased hydrophobicity, had higher activity against Gram-positive bacteria, but also showed hemolytic and destructive effects on eukaryotic cells. Contrary, anoplin[2-6] with a similar charge and amphipathicity as natural anoplin, effectively killed Gram-negative bacteria, also pathogenic drug-resistant strains, without being hemolytic and toxic to eukaryotic cells. Our results showed that anoplin charge, amphipathicity, and location of hydrophobic residues affect the peptide destructive activity on the cell wall, and thus, its antibacterial activity. This means that by manipulating the charge and position of the staple in the sequence, one can manipulate the antimicrobial activity.